Investigation of blast and fragmentation loading characteristics – Field tests. (15th July 2018) - Grisaro, Hezi Y.; Benamou, David; Dancygier, Avraham N.
Highlights: Reinforced concrete (RC) T-walls elements were exposed to cased charge detonations. The combined loading characterization has been experimentally studied and analyzed. The structural damage of the RC walls due to the fragmentation impact was measured. Most of the damage was created by the fragmentation impact. The fragment effect has to be considered and cannot be ignored. Abstract: The combined loading of blast and fragments on reinforced concrete (RC) elements has been studied in field tests of RC T-walls that were subjected to detonated cylindrical cased charges. Characterization of the combined loading has been experimentally studied and analyzed. This analysis includes the pressure time-history of a control bare charge and of the cased charges, the relation between them, and the distribution of the fragment masses and velocities over a vertical barrier that was impacted by them. The structural damage of the RC walls due to the fragmentation impact was also measured. The results indicate that while the detonation of a bare charge, without a casing, yielded negligible structural damage, major damage was caused due to the impact of the fragments. The importance of the findings that are reported in the paper relates to design of protective structures that are prone to be subjected to extreme loads caused by cased charges. Commonly, except for very small standoff distances, the fragments will reach the structure before the blast wave, which means that the damage that is created by the fragments should be considered for the global analysis of the element response to the blast load. Furthermore, the results reported here show that the smaller the standoff distance, the more significant the damage influence is on the response of the structure.